PENGARUH PERAN MANAJEMEN LOGISTIK UNTUK MENINGKATKAN EFISIENSI DISTRIBUSI DI PT BAHARI UTAMA SAMUDRA - Jaya Saputra, Toto Dwi; Widhi Yanti, Dyah Agustin (Unitri Press, 2025)
This research aims to examine the role of logistics management in increasing distribution efficiency at PT Bahari Utama Samudra. Through a case study approach, this research identifies the factors that influence logistics performance, the obstacles faced, and the strategies implemented to optimize the distribution process. The research results show that implementing tracking technology, optimizing delivery routes, and proper inventory management can significantly increase a company's operational efficiency.